Acceleration‐induced acute type A aortic dissection in the sky: 10‐year follow‐up. Issue 5 (16th March 2020) - An, Jun; Elhenawy, Abdelsalam M.
Abstract: Acute aortic dissection is uncommon, but can turn into a fatal disease if not managed quickly. A 49‐year‐old male fighter pilot presented to us after sudden excruciating chest pain during a flight at the moment of an acute spiral down action. A contrast‐enhanced computed tomography angiography showed Stanford type A aortic dissection that required surgical ascending aorta and hemiarch replacement with uneventful postoperative recovery and 10‐year follow‐up. Here, we presented the first report of a previously healthy pilot developed acute aortic dissection in the sky. Physicians should be aware of such a case that might happen more common with rapid aviation progress.